Dispersed phase volume fraction, weak acids and Tween 80 in a model emulsion: Effect on the germination and growth of Bacillus weihenstephanensis KBAB4 spores. (July 2018) - Léonard-Akkari, Lucie; Guégan, Stéphanie; Courand, Fabienne; Couvert, Olivier; Lepage, Jean-François; Rondeau-Mouro, Corinne; Desriac, Noémie; Mathot, Anne-Gabrielle; Leguérinel, Ivan; Coroller, Louis; Decourcelle, Nicolas
Abstract: In foodstuffs, physico-chemical interactions and/or physical constraints between spores, inhibitors and food components may exist. Thus, the objective of this study was to investigate such interactions using a model emulsion as a microbial medium in order to improve bacterial spore control with better knowledge of the interactions in the formulation. Emulsions were prepared with hexadecane mixed with nutrient broth using sonication and were stabilized by Tween 80 and Span 80. The hexadecane ratio was either 35% (v/v) or 50% (v/v) and each emulsion was studied in the presence of organic acid (acetic, lactic or hexanoic) at two pH levels (5.5 and 6). Self-diffusion coefficients of emulsion components and the organic acids were measured by Pulsed Field Gradient-Nuclear Magnetic Resonance (PFG-NMR). The inhibition effect on the spore germination and cell growth of Bacillus weihenstephanensis KBAB4 was characterized by the measure of the probability of growth using the most probable number methodology, and the measure of the time taken for the cells to germinate and grow using a single cell Bioscreen® method and using flow cytometry. The inhibition of spore germination and growth in the model emulsion depended on the dispersed phase volume fraction and the pH value. The effect of the dispersed phase volume fraction was due to a combination of (i) the lipophilicity of the biocide, hexanoic acid, that may have had an impact on the distribution of organic acid between hexadecane and the aqueous phases and (ii) the antimicrobial activity of the emulsifier Tween 80 detected at the acidic pH value. The interface phenomena seemed to have a major influence. Future work will focus on the exploration of these phenomena at the interface. Graphical abstract: Highlights: Bacterial growth in emulsion depends on interactions (cells/inhibitors/components). A model emulsion was used as a microbial medium to investigate these interactions. A combination of effects affected microbial development in emulsion. The lipophilicity of the weak acid had an impact on its distribution in emulsion. An antimicrobial activity of the emulsifier was detected at the acidic pH value.